Determination of the lactose and galactose content of common foods: Relevance to galactosemia. Issue 11 (19th July 2022) - Shakerdi, Loai A.; Wallace, Leonie; Smyth, Georgina; Madden, Nora; Clark, Anne; Hendroff, Una; McGovern, Marianne; Connellan, Sarah; Gillman, Barbara; Treacy, Eileen P.
Abstract: Classical galactosemia (CG) is a disorder of galactose metabolism which results from deficiency of the enzyme galactose‐1‐phosphate uridylyl transferase (GALT). Treatment consists of immediately eliminating galactose from the diet in the new‐born and lifelong restriction of dietary galactose. The inclusion of a wider variety of foods for people with CG may provide many benefits, including improved nutritional adequacy and quality of life. Galactose plays an important role in glycosylation of glycoproteins and glycolipids. Moderate liberalization of galactose restriction has been shown to improve immunoglobulin G (IgG) glycosylation for some individuals with CG. Moreover, recent outcome research suggests that strict restriction of nondairy galactose may have more unfavorable outcomes than moderate liberalization in CG patients. In the current work, based on patient feedback, we have analyzed the lactose and galactose content of different foods available in Ireland. These include a range of cheeses, yogurts, pizzas, soups, biscuits, cakes, pastries, crackers, mayonnaises, salad creams, fat spreads, crisps, corn chips, salamis, and gravies. This work provides information to support the development of a practical food‐based approach to facilitate analysis of dietary galactose intake and to possibly increase overall variety of food choices for people with CG. Abstract : In this work we have analysed the galactose content of commonly available foods in Ireland to provide more accurate information on galactose and lactose contents. This information is heretofore lacking and will provide valuable information to the international Galactosaemia community; and also, for researchers and clinicians in the field of Human Nutrition.